Problematika Pemenuhan Hak Korban Tindak Pidana: Miskonsepsi Terminologi Restitusi (Analisis Teori Konstruksi Sosial) - Mahmud Mulyadi; Rafiqoh Lubis; Rosmalinda; Rangkuti, Liza Hafidzah Yusuf (Universitas Muhammadiyah Surabaya, 2024)
Restitution rights are problematic in fulfilling the rights of victims of crime, mainly due to misconceptions about restitution terminology. This research aims to explore and analyze the misconceptions of restitution terminology by the society and its impact on the fulfillment of the rights of victims of crime using the analysis of Social Construction Theory. This research uses an empirical juridical approach by utilizing primary data in the form questionnaires distributed to community service participants and the focused discussion process in Community Service activities and secondary data in the form of primary, secondary and tertiary legal materials. The findings of this study indicate that the misconception of restitution terminology is formed through the social construction of legal norms on the wrong meaning of restitution terminology These misconceptions take the form of restitution being understood as peace, restitution is the same as compensation and restitution results in the elimination of imprisonment for the perpetrator. These misconceptions have implications for the non-fulfillment of the rights of victims of crime, which will arrise in the difficulty in submitting requests for restitution, the victim's perception of justice is reduced and a negative impact on the victim's recovery process. This misconception will also lead to weak law enforcement against criminal offenders.